2009
DOI: 10.1055/s-0029-1220780
|View full text |Cite
|
Sign up to set email alerts
|

Two Dose Regimens of Nifedipine for Management of Preterm Labor: A Randomized Controlled Trial

Abstract: We compared two dose regimens of tocolytic oral nifedipine. Women with singleton pregnancies admitted in preterm labor (24 to 34 weeks) were randomized to high-dose (HD) nifedipine ( N = 49; 20 mg loading dose, repeated in 30 minutes, daily 120 to 160 mg slow-release nifedipine for 48 hours followed by 80 to 120 mg daily until 36 weeks) or low-dose (LD) nifedipine ( N = 53; 10 mg, up to four doses every 15 minutes, daily 60 to 80 mg slow-release nifedipine for 48 hours followed by 60 mg daily until 36 weeks). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…No participant received maintenance tocolysis therapy when uterine contractions ceased. The loading dose of nifedipine (Nidilat; Sanofi Aventis, Istanbul, Turkey) was administered as a 10‐mg oral capsule every 15 minutes within the first hour . Maternal pulse and blood pressure were monitored after each capsule was administered.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…No participant received maintenance tocolysis therapy when uterine contractions ceased. The loading dose of nifedipine (Nidilat; Sanofi Aventis, Istanbul, Turkey) was administered as a 10‐mg oral capsule every 15 minutes within the first hour . Maternal pulse and blood pressure were monitored after each capsule was administered.…”
Section: Methodsmentioning
confidence: 99%
“…The present prospective, self-controlled observational study was per- was administered as a 10-mg oral capsule every 15 minutes within the first hour. 10 Maternal pulse and blood pressure were monitored after each capsule was administered. Betamethasone (Celestone Cronodose; Schering-Plough, Istanbul, Turkey) was administered as two intramuscular doses of 12 mg each, administered 24 hours apart.…”
Section: Methodsmentioning
confidence: 99%
“…The appropriate dose of nifedipine for tocolysis is still under investigation. In a comparison of two dose regimens of oral nifedipine in a study on threatening PTB between gestational weeks 24 and 34, it was found that a high dose of the drug (20 mg loading dose, daily 120–160 mg for 48 hours, followed by 80–120 mg daily up to 36 weeks) did not have any advantage over a low dose (10 mg loading dose, daily 60–80 mg for 48 hours, followed by 60 mg daily up to 36 weeks) as regards uterine quiescence [34]. In a small Bulgarian study, nifedipine (40 mg four times daily) delayed a large majority of the pregnancies (32 out of 41) with early contractions until normal term, without significant side-effects [35].…”
Section: The Efficacy Of Ccbs Against Ptbmentioning
confidence: 99%
“…One randomized controlled trial evaluated the difference between two dose protocols of tocolytic oral nifedipine. 73 One hundred two women were randomized to receive one of two regimens, the high-dose or the low-dose oral nifedipine. In the high-dose group, women were given a loading dose of 20 mg of crushed nifedipine sublingually, and in case uterine activity persisted, another equal loading dose was given after 30 minutes.…”
Section: Protocol For Dosing and Administration Of Nifedipine For Acumentioning
confidence: 99%